Performance analysis of wireless communication networks with threshold activation process and interference signals. (1st May 2020) - Yu, Xiangran; Ma, Zhanyou; Guo, Shanshan; Chen, Li
In order to reduce energy consumption in wireless communication networks, the sleep mode in the energy saving strategy and the threshold activation process of the base station are considered. Combining with practice, the existence of interference signals and possible errors in the transmission of data packets are considered. At the same time, considering that the wireless communication network system has two channels and one of them is incompletely reliable, a queuing model of repairable M/M/2 multiple working vacations with start-up period, negative customers, feedback and N-strategy is established. Using quasi birth-and-death process (QBD) and Gauss-Seidel iterative method, the expressions of the average delay of the data packet and other performance indicators are given. Then, using MATLAB software for numerical analysis, the influence of system parameters on the average delay and other performance indicators is analysed. Finally, the social optimal parameters are found by constructing benefit functions.